Analisis Pengaruh Penggunaan QRIS Terhadap Perilaku Konsumsi Mahasiswa Program Studi Ekonomi Angkatan 2021 Di Universitas Nurul Jadid - Sulistiana, Erinda; Wulandari, Evi Sri; Pramita, Riska Dwi (BISMA : Business and Management Journal, 2024)
The use of QRIS tends to influence the consumption behavior of 2021 Economics Study Program students at Nurul Jadid University. This research aims to further explore the influence of using QRIS on consumption behavior among students as well as the benefits obtained from using QRIS. This research uses a qualitative approach, where researchers directly conduct interviews, observations and documentation as data collection tools. The population studied was students from the Economic Study Program Class of 2021 at Nurul Jadid University. The interview results revealed that: (1) The use of QRIS tends to influence students' consumption behavior. (2) Using QRIS provides convenience for both buyers and sellers. (3) Payment via QRIS can reduce the risk of losing money, offer special offers and discounts, and help students track their expenses. The conclusion is that the use of QRIS influences the consumption behavior of 2021 Economics Study Program students at Nurul Jadid University and also provides convenience for sellers. Apart from that, using QRIS helps some students get special offers and discounts and makes it easier for them to track expenses.